2019
DOI: 10.1152/ajprenal.00254.2019
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of long noncoding RNA XIST protects against renal interstitial fibrosis in diabetic nephropathy via microRNA-93-5p-mediated inhibition of CDKN1A

Abstract: Long noncoding RNAs (lncRNAs) have been reported to play an important role in diabetic nephropathy (DN). However, the molecular mechanism involved in this process remains poorly understood. Thus, the present study aimed to explore the function and molecular mechanism of dysregulated lncRNA X-inactive specific transcript (XIST) in DN. DN mouse models were established by streptozotocin treatment, and human renal tubular epithelial HK-2 cells were exposed to high glucose to produce an in vitro model. XIST was hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 29 publications
2
51
1
Order By: Relevance
“…Many studies have reported that lncRNAs participate in DN through regulating target gene expression 20,21 . For example, silencing of the lncRNA XIST contributed to preventing renal interstitial fibrosis in DN 22 . Ge et al 23 also found that overexpression of the lncRNA NR_038323 regulated renal fibrosis via the miR‐324‐3p/DUSP1 axis in DN.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported that lncRNAs participate in DN through regulating target gene expression 20,21 . For example, silencing of the lncRNA XIST contributed to preventing renal interstitial fibrosis in DN 22 . Ge et al 23 also found that overexpression of the lncRNA NR_038323 regulated renal fibrosis via the miR‐324‐3p/DUSP1 axis in DN.…”
Section: Discussionmentioning
confidence: 99%
“…The lncRNAs are a newly recognized mechanism for gene regulation and are being explored as potential therapeutic targets in a variety of diseases (Li et al, 2018;Pecero et al, 2019;Wang et al, 2020), including diabetic nephropathy (Ge et al, 2019;Yang et al, 2019). A nucleic acid-based approach could allow greater specificity than pharmacological compounds, reducing side effects and allowing tissue-specific delivery (Sharma and Watts, 2015;Ku et al, 2016).…”
Section: Figure 8 | Ko Of Edn1-as Regulatory Elements Results In Incrmentioning
confidence: 99%
“…In renal tissues of DN patients, DN mice, and high glucose-exposed HK-2 cells, lncRNA X-inactive specific transcript (XIST) was found to be highly increasing. Downregulated expression of XIST led to an increase in miR-93-5p expression, thereby decreasing CDKN1A and suppressing renal interstitial fibrosis in DN [85]. Overall, although the potential role of lncRNAs in the pathogenesis of DN has not been fully understood, emerging evidence shows the importance of lncRNAs in the progression of DN.…”
Section: Lncrnas In Dnmentioning
confidence: 99%